Longitudinal Trends in Physical Activity Among Older Adults With and Without HIV in Uganda - Ratnayake, Aneeka; Tong, Yao; Reynolds, Zahra; Chamut, Steffany; Quach, Lien T.; Mbabazi, Phoebe; Sagar, Shruti; Maling, Samuel; North, Crystal M.; Passell, Eliza; Yoo-Jeong, Moka; Tsai, Alexander C.; et al. (SAGE Publications, 2026)
IntroductionPhysical Activity (PA) and its links to frailty, quality of life (QoL), and other comorbidities in older Ugandans living with HIV remain under-explored.MethodsWe analyzed data from three annual assessments of older people living with HIV (PLWH) and age- and sex-similar people not living with HIV (PnLWH). We fitted linear generalized estimating equations (GEE) regression models to estimate the correlates of PA, including demographics, frailty, QoL, HIV, and other comorbidities.ResultsWe enrolled 297 PLWH and 302 PnLWH. Older age (b = -157.34, 95% CI [-222.84, -91.83]), living with HIV (b = -979.88 [95% CI: -1878.48, -81.28]), frailty (b = -3011.14 [95% CI: -4665.84, -1356.45]), and comorbidities (b = -2501.75 [95% CI: -3357.44, -1646.07]) were associated with lower overall PA. Higher general QoL (b = 89.96 [95% CI: 40.99, 138.94]) was associated with higher PA.ConclusionPA interventions may support wellbeing of older people in the region, and tailored interventions should be explored. MEDLINE
Keywords: HIV; older adults; Uganda; physical activity; frailty; quality of life